Is anterior cruciate ligament reconstruction necessary for the non-sporting population? - Manandhar, Rajeev Raj; Khanal, Krishna Raj; Gautam, Saroj; Gupta, Aman; Khanal, Himal; Bhusal, Suraj (Journal of Kathmandu Medical College, 2022)
Background: Anterior cruciate ligament injury (ACL) is a common injury in both sporting and non-sporting population. All patients with an ACL injury may not require surgery. The criteria for deciding whether a reconstruction should be performed are not absolute and the trend is to offer reconstruction to the sporting population as they require a stable knee to perform in their line of work. The non-sporting population also require a stable knee to perform their daily activities. Objectives: To assess functional outcome in the non-sporting patients following reconstruction. Methods: A prospective observational analytical study was conducted in the age group from 18 to 55 years, with symptomatic ACL injury who were not involved in sporting activities from July 2020 to December 2021. Fifty patients participated in the study. Convenience sampling technique was used. The IKDC and Lysholm scores were used preoperatively and six months post-operatively to assess the benefit of the treatment. Results: Out of 50 patients, four were lost to follow up. Out of total 46 patients, 29 (63.04%) patients were male and 17 (36.96%) patients were female. The mean age of patients was 31.61 ± 7.38 years. The IKDC and Lysholm scores measured preoperatively were 47.07 ± 7.51 and 52.17 ± 7.91 and the six-month post-operative scores were 86.73 ± 5.54 and 90.69 ± 4.63 respectively. Conclusion: The patients from the non-sporting population who underwent ACL reconstruction had significantly improved IKDC as well as Lysholm scores compared to their function prior to the procedure.